Determinants of employees' financial well-being: the moderation effect of working sector - Sabri, Mohamad Fazli; Falahati, Leila; Masud, Jariah; Paim, Laily (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The purpose of this study is to examine factors affecting financial well-being among public and private employees in Malaysia. The results of this study can be used for better understanding on the relationships between and among determinants of financial well-being by highlighting the relationships among financial literacy, financial behavior, financial management, financial problems, and financial stress. Samples were selected using multi-stage sampling technique among employees in public and private sectors. A total of 2,000 completed questionnaires were analyzed using path analysis to identify direct and indirect effects on financial well-being. The results indicate that financial behavior, financial management, financial problems and financial stress are significant predictors of financial well-being among employees in public and private sectors. In contrast, financial literacy contributes to predict financial well-being among public sectors but not among private sectors. Findings from this study have important implication with respect to the need of workplace financial education.